El problema de la donación en la fenomenología de J.-L. Marion - Roggero, Jorge (2019)
“The Question of Givenness in Jean-Luc Marion’s Phenomenology”. Marionian phenomenology has received various critiques regarding its reading of the Husserlian and Heideggerian Gegebenheit. This article aims to account for the phenomenological importance of the Marionian conception of givenness.